2008
DOI: 10.1103/physrevlett.100.087204
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling Anisotropic Magnetoresistance in Multilayer-(Co/Pt)/AlOx/PtStructures

Abstract: We report observations of tunneling anisotropic magnetoresitance (TAMR) in vertical tunnel devices with a ferromagnetic multilayer-(Co/Pt) electrode and a non-magnetic Pt counter-electrode separated by an AlOx barrier. In stacks with the ferromagnetic electrode terminated by a Co film the TAMR magnitude saturates at 0.15% beyond which it shows only weak dependence on the magnetic field strength, bias voltage, and temperature. For ferromagnetic electrodes terminated by two monolayers of Pt we observe order(s) o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
87
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 25 publications
3
87
1
Order By: Relevance
“…For CoPt film, the anisotropy in tunneling DOS was predicted 11 to be >12%. This was confirmed 8 by exploiting the enhanced SOC at the interface with CoPt based electrodes giving rise to large TAMR of 15%. Although the TAMR effect may be small in magnitude in tunnel contacts with transition metal FMs, it may influence the spin injection from a FM into a semiconductor (SC).…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…For CoPt film, the anisotropy in tunneling DOS was predicted 11 to be >12%. This was confirmed 8 by exploiting the enhanced SOC at the interface with CoPt based electrodes giving rise to large TAMR of 15%. Although the TAMR effect may be small in magnitude in tunnel contacts with transition metal FMs, it may influence the spin injection from a FM into a semiconductor (SC).…”
Section: Introductionmentioning
confidence: 52%
“…A feature that provides more insight is the anisotropy of the tunnel conductance, which may have various sources, including the TAMR. Previous reports on TAMR concluded that the change in tunnel resistance is due to the anisotropy in DOS [3][4][5]8,9,11,21 at the tunnel interface between a FM and an insulating barrier. As the magnetization direction is rotated, it faces different DOS, thereby changing the transport across the tunnel contact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a metal/oxide bilayer is already half of an MTJ, which could be used as a readout element of a magnetic bit where the write functions are performed by the SO torque [15]. Moreover, several studies have pointed out the interplay between SO coupling and tunnelling anisotropic magnetoresistance in MTJs [99][100][101] and explicitly considered the dependence of the tunnelling conductance on interfacial Rashba spin splitting in metal systems [102,103] as well as the coexistence of Dresselhaus and Rashba fields in metal/semiconductor heterojunctions [31,65,104], providing additional functionalities to layers displaying strong SO effects. Further, as noted by Obata & Tatara [59], DW manipulation can be achieved by means of an SO torque, depending on the type of DW involved and easy axis magnetization direction, which may be useful in, for example, shift register or random access memory applications based on DW motion.…”
Section: Discussionmentioning
confidence: 99%
“…Low Curie temperatures have prevented the direct integration of (III,Mn)V FM semiconductors into spintronic technologies. Nevertheless, new phenomena discovered in (Ga,Mn)As have been subsequently reported in the room-temperature metal FMs, relevant not only for basic science but also for practical spintronic applications [14][15][16] .…”
mentioning
confidence: 99%